Development of functional almond milk beverage with probiotic Lactiplantibacillus plantarum and Lactiplantibacillus brevis bacteria - Bekiroglu, Hatice; Cakir, Elif; Dertli, Enes; Sagdic, Osman (Walter De Gruyter Gmbh, 2025)
This study investigated the quality characteristics of a plant-based functional beverage produced by fermenting almond milk with the probiotic strains Lactiplantibacillus plantarum (WLPL), Lactiplantibacillus pentosus (WLPE), and their combination (WLP). The dry matter, ash, protein, and fat contents of the fermented beverages were found to range from 6.55 % to 7.98 %, 0.20 % to 0.27 %, 3.27 % to 5.12 %, and 3.05 % to 3.91 %, respectively. Among the formulations, the WLP beverage exhibited the highest total phenolic content (758.8 mg GAE/L). The highest antioxidant activity was observed in the WLPE fermented beverage. Furthermore, the probiotic bacterial count remained above 8 log CFU/mL in all fermented samples for up to 14 days, indicating the sustained viability of the probiotic strains. After 14 days of storage, the beverage fermented with a combination of Lactiplantibacillus plantarum and Lactiplantibacillus pentosus was the most preferred by consumers, with notable differences in the color profiles of the various fermented beverages.
Keywords: vegan beverages; antioxidant capacity; phenolic content; sensory properties